Preparation method, application and testing device and method of high-temperature heat dissipation material Ti-6Al-4V
By ablation of the surface of Ti-6Al-4V material by femtosecond laser, V-shaped grooves and micro-nano structures are formed, which solves the problem of material wettability under high temperature conditions, and achieves efficient evaporation and heat dissipation effect. It is suitable for high-temperature M-cycle Cooling technology.
Patent Information
- Application Number
- CN202411377165.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-30
- Publication Date
- 2025-02-14
AI Technical Summary
In the existing high-temperature M-cycle cooling technology, it is difficult for the material to maintain wettability under high temperature conditions, which affects the heat dissipation efficiency.
The surface of Ti-6Al-4V material is ablated by femtosecond laser, forming parallel V-shaped grooves and rich micro-nano structures to increase the surface area of the material and improve wetting performance.
Under high temperature conditions above 230°C, the material surface still maintains super wetting performance, achieving efficient evaporation and heat dissipation, and is suitable for high-temperature M-cycle cooling technology.
Smart Images

Figure CN119426809A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of M-cycle cooling materials, and in particular to a preparation and testing device and method of a Ti-6Al-4V metal material having super wettability and strong evaporation performance at a high temperature of 230°C. Background Art
[0002] Thermal power plants, cars, trucks, buses, airplanes, and ships powered by fossil fuels are the main sources of major environmental pollutants such as CO, CO2, SO2, and ozone. These pollutants have changed the Earth's climate and caused global warming. Scientific research shows that if effective measures are not taken to reduce anthropogenic greenhouse gas emissions, the Earth's ecosystem will face serious changes. In order to reduce the emission of environmental pollutants on a global scale, it is urgent to improve the power generation efficiency and fuel utilization efficiency of power plants.
[0003] Recent theoretical studies have shown that the application of M-cycle evaporative cooling system in power plants can significantly improve power generation efficiency. Some studies have pointed out that in coal-fired power plants, the application of M-cycle cooling technology has increased thermal efficiency from 35% to 40% or even higher; in gas turbines, combined with M-cycle cooling technology, the system efficiency can be increased to 42%-45%. Through waste heat recovery, the improvement of power generation efficiency makes the performance of the overall power generation system optimal; power plants using M-cycle cooling technology usually reduce nitrogen oxide and carbon dioxide emissions by about 10%-25% compared with traditional systems. After using M-cycle cooling technology, not only the thermal efficiency is improved, but also the electricity cost is reduced by about US$3.8 per megawatt-hour, showing its dual advantages of economy and efficiency. Although M-cycle technology has shown its superiority, high-temperature M-cycle cooling technology is rarely used compared with low-temperature cooling technology. The main reason restricting its development is that it is difficult for materials to maintain wettability under high temperature conditions greater than 150°C. Therefore, it is crucial to develop materials that maintain stable wettability when the surface temperature of the material is greater than 150°C.
[0004] Although significant progress has been made in the research and development of materials for high-temperature M-cycle cooling technology, such as using chemical coating technology to modify materials, using high-performance composite materials, creating microchannels on the surface of materials, and changing coolants to increase the upper temperature limit; however, the above methods all have different defects. Chemical coatings can easily cause damage to the human body and the environment. The manufacturing costs of high-performance composite materials and surface microchannels are too high and difficult to promote on a large scale. The change of coolant not only has the risk of leakage, but also has a higher cost than the commonly used liquid water coolant.
[0005] After searching, the application publication number CN112251635B is a high thermal stability equiaxed nanocrystalline Ti6Al4V-Ni alloy and its preparation method. The chemical composition of the titanium alloy is as follows (weight %): Al: 5.0-7.0; V: 3.0-5.0; Ni: 0.01-4.8; the balance is Ti. The preparation method of the titanium alloy is as follows: first, after keeping it above 950°C for a period of time, it is quickly cooled to room temperature to obtain a nano-lath precursor; then the nano-lath precursor is subjected to a temperature of 720-840°C and a strain rate of 0.1-5s -1 Thermal deformation is performed within a range of , and the total strain is greater than or equal to 70%, so that the nano-lath precursor is transformed into an equiaxed nano-crystalline structure.
[0006] CN112063893B, a high thermal stability equiaxed nanocrystalline Ti6Al4V-Fe alloy and its preparation method. The chemical composition of the titanium alloy is as follows (weight %): Al: 5.0-7.0; V: 3.0-5.0; Fe: 0.01-4.0; the balance is Ti. The preparation method of the titanium alloy is as follows: first, after being kept at a temperature above 950°C for a period of time, it is quickly cooled to room temperature to obtain a nano-lath precursor; then the nano-lath precursor is thermally deformed at a temperature of 650-850°C and a strain rate of 0.1-5s-1, and the total strain is greater than or equal to 70%, so that the nano-lath precursor is transformed into an equiaxed nanocrystalline structure.
[0007] High thermal stability equiaxed nanocrystalline Ti6Al4V-Fe alloy prepared in CN112063893B patent
[0008] , has excellent comprehensive mechanical properties and unique physical and chemical properties, solves the problem that the thermal stability of nanocrystalline metal materials decreases significantly under high temperature conditions, causing the materials to lose their original excellent properties, but does not show its wettability under high temperature conditions, and the high-temperature M-cycle cooling technology is highly dependent on phase change heat dissipation and has extremely high requirements for the wettability of materials. The high-temperature heat dissipation material Ti-6Al-4V of the present invention uses femtosecond laser ablation of the Ti-6Al-4V material surface to obtain a series of parallel V-shaped grooves, and a large number of irregular micro-nano structures distributed on the grooves make the material surface still have extremely strong wettability at high temperatures. Compared with the equiaxed nanocrystalline Ti6Al4V-Fe alloy in CN112063893B, the high-temperature heat dissipation material Ti-6Al-4V of the present invention not only has the excellent mechanical properties and physical and chemical properties of the titanium alloy material itself, but also has super wettability at high temperatures. Under high temperature conditions, water is vertically pumped to the upper surface of the material against gravity, forming a stable film evaporation on the surface of the material, achieving efficient heat dissipation effect, and providing favorable conditions for phase change heat dissipation in M-cycle cooling technology at high temperatures.
[0009] In view of this, this application is hereby filed. Summary of the invention
[0010] The present invention aims to solve the above problems of the prior art. A high-temperature heat dissipation material Ti-6Al-4V and its preparation method, application and testing device and method are proposed. The technical solution of the present invention is as follows:
[0011] A high-temperature heat dissipation material Ti-6Al-4V, wherein the titanium-aluminum-vanadium alloy Ti-6Al-4V material is composed of titanium: 90.7%-91.7%, aluminum: 5.5%-6.75%, vanadium: 3.5%-4.5%, and has a thermal expansion coefficient of 8.6×10 -6 / K, its density is 4.43g / cm 3 , high temperature melting point is above 1660℃, hardness is 300HB, specific heat capacity is 0.52J / g·K.
[0012] Furthermore, the surface of the Ti-6Al-4V material has a plurality of parallel and continuously distributed V-shaped grooves, the groove depth of the Ti-6Al-4V material is 50 to 60 μm, the spacing between adjacent grooves is 90 to 100 μm, and the groove surface of the material has a rich micro-nano structure of 10 nm to 200 μm.
[0013] Furthermore, the material Ti-6Al-4V is processed by femtosecond laser ablation; the femtosecond laser ablation is performed in a clean room with a constant temperature of 23° C. and a constant humidity of 50%.
[0014] Furthermore, the femtosecond laser ablation parameters are: laser energy density 7J / cm 2 , the step length between scan lines is 100 μm, the pulse repetition frequency is 1000 Hz, and the scanning speed is 0.5 mm / s.
[0015] A method for preparing Ti-6Al-4V based on any one of the materials described, comprising the following steps:
[0016] (1) The polished Ti-6Al-4V material was placed in an ultrasonic cleaner and cleaned with deionized water for 3 minutes;
[0017] (2) Place the cleaned and polished Ti-6Al-4V material on a femtosecond laser displacement platform;
[0018] (3) In a clean room with a constant temperature of 23°C (±0.5°C) and a constant relative humidity of 50% (±2%), a femtosecond laser was used to ablate the surface of the Ti-6Al-4V material; the laser ablation parameters were: laser energy density 7 J / cm 2, the step length between scan lines is 100 μm, the pulse repetition frequency is 1000 Hz, the central wavelength is 800 nm, and the scanning speed is 0.5 mm / s;
[0019] (4) A Ti-6Al-4V material having a plurality of parallel and continuously distributed groove structures is obtained, wherein the groove depth is 50 to 60 μm and the spacing between adjacent grooves is 90 to 100 μm.
[0020] An application of the material Ti-6Al-4V based on any one of the above, wherein the material Ti-6Al-4V is used for heat dissipation in a high-temperature M-cycle heat and mass exchanger.
[0021] An evaporation rate testing device based on any of the materials Ti-6Al-4V described above, comprising: a high-precision balance, a temperature sensor, a heating plate, a heating plate console, a high-speed camera and an infrared thermal imager: wherein the high-precision balance is used to accurately measure the mass m1 of deionized water before evaporation and the mass m2 of deionized water after evaporation in a water container; the temperature sensor is used to detect the real-time surface temperature of the Ti-6Al-4V material during the evaporation process, and calibrate the digital temperature displayed on the heating plate console to ensure the accuracy of the material surface temperature; the heating plate is used to provide heat to the Ti-6Al-4V material close to the heating plate; the heating plate console is used to digitally control the heating of the Ti-6Al-4V material by the heating plate, so that the material surface temperature is stably maintained at a set temperature; the high-speed camera is used to observe the water film state of different wetting areas on the surface of the Ti-6Al-4V material under high temperature; and the infrared thermal imager is used to observe the temperature gradient distribution on the surface of the Ti-6Al-4V material under high temperature.
[0022] A testing method based on the evaporation rate testing device comprises the following steps:
[0023] 1) Clamp the sample vertically against the heating plate, and place a partially open rectangular water container at the lower end;
[0024] 2) Place high temperature resistant PTFE material in a small area on the upper right side of the sample to make the temperature sensor close to the sample;
[0025] 3) Heat the heating plate close to the material to the set temperature through the digital visual heating table controller;
[0026] 4) Inject 90% to 95% of the capacity of the rectangular water container with deionized water, record the initial mass m1 of the water container, make the water container contact the bottom of the material, and record the starting time t1;
[0027] 5) Record the wetted surface area S1 of the sample;
[0028] 6) Record the stopping time t2 and quickly measure its mass m2;
[0029] 7) Calculate the evaporation rate of Ti-6Al-4V material at different temperatures and wind speeds according to the formula:
[0030]
[0031] 8) Use a high-speed camera and an infrared thermal imager to observe and record the water film state in different areas of the sample. The advantages and beneficial effects of the present invention are as follows:
[0032] Generally speaking, when the surface temperature of the material is 100°C higher than the boiling point of liquid water, the macroscopic wettability of the material will be greatly reduced. This is because when liquid water contacts a surface with a higher boiling point than its boiling point, the liquid forms a vapor film and does not evaporate immediately. Directly dropping liquid water on the surface of a high-temperature material will show that the droplets are suspended and move rapidly on the hot surface without directly contacting the hot surface. The bottom of the liquid will quickly heat to the boiling point to form a large amount of steam, which forms an isolation layer between the droplets and the hot surface. This allows the droplets to "glide" on the surface instead of evaporating directly. The evaporation rate test device of the present invention avoids the occurrence of the above-mentioned Leidenfrost phenomenon. Based on the rich micro-nano structure on the surface of the material, it still exhibits excellent super-wetting properties even at a high temperature of 230°C, and the liquid water in the water container at the bottom of the material is pumped to the upper surface of the material to form a stable thin film evaporation.
[0033] It is difficult to ensure that the Ti-6Al-4V material has efficient heat dissipation capability only by showing super-wetting performance at high temperature on a macro scale. In order to detect whether the Ti-6Al-4V material still has high evaporation efficiency at a high temperature above 150°C, the present invention provides a method for testing the evaporation rate of the Ti-6Al-4V material. First, the heating plate controlled by the heating plate console is tightly attached to the surface of the material and the bottom of the material is placed in a water container containing 95% deionized water to ensure that the surface temperature of the material is accurately controlled by the heating plate console. The Ti-6Al-4V material reaches a dynamic balance of the water film under the strong capillary force and the downward gravity of the water. At this time, the material surface evaporation rate is recorded and calculated. It is worth noting that the wetted area S1 of the material surface used for calculation is obtained by recording its projected area, processing it in the XARA software, calculating its ratio to the total area of the material, and then amplifying it in proportion. All other data are direct values obtained from experimental tests.
[0034] In addition, in order to explain the efficient evaporation rate of the material, during the material evaporation rate test, its stable water film state was photographed by a high-speed camera and infrared images were recorded in real time.
[0035] Generally speaking, the wetting of materials is not stable, but a dynamic process. It will go through three states: thick film, thin film, and ultra-thin film. The ultra-thin film is extremely short-lived due to its very efficient evaporation rate. High-magnification high-speed camera images and infrared thermal imager images show that at high temperatures above 150°C, liquid water can still be adsorbed on the surface of the material to form a stable thin water film. According to the thin film evaporation theory, as the water film changes from thick film-thin film-ultra-thin film stage, its evaporation rate increases exponentially. The ultra-thin film state is extremely unstable due to its very high evaporation rate and extremely short duration, and it is difficult to apply in practice. The stable thin film state also shows a very high evaporation rate. The water film on the surface of the material in the stable thin film state will form more meniscus structures, and the ultra-thin film wetting of micro-nano structures such as nanopillars, nanopores and nanoclusters on the grooves on the surface of the material also further improves the evaporation efficiency of the material. It is worth noting that when the surface temperature of the material is higher than the boiling point of water by 100°C, no boiling bubbles are observed in the high-speed camera.
[0036] Compared with the prior art, the present invention has the following advantages and beneficial effects:
[0037] 1. An embodiment of the present invention provides a method for preparing a Ti-6Al-4V material with high-efficiency heat dissipation performance at high temperature. The surface of the super-wetting and strongly evaporating Ti-6Al-4V material at high temperature is ablated by a femtosecond laser to have a series of parallel micron-sized V-shaped grooves. The grooves are distributed with rich micro-nano structures to increase the actual surface area of the material, improve the evaporation rate of the material surface, and facilitate evaporative heat dissipation at high temperature.
[0038] 2. The Ti-6Al-4V material with efficient heat dissipation performance at high temperature provided by the embodiment of the present invention still has super wetting performance at high temperature above 230°C. At present, thin film evaporation is difficult to maintain stability due to its efficient evaporation performance. However, the experiment of the present invention proves that the Ti-6Al-4V material still maintains stable thin film evaporation at a high temperature of 230°C. Therefore, the Ti-6Al-4V material of the present invention can be well adapted to the application of M-cycle cooling technology at high temperature under high temperature conditions.
[0039] 3. The embodiment of the present invention provides a testing device and method for Ti-6Al-4V material with efficient heat dissipation performance. The heating plate close to the material is digitally and accurately controlled by the heating plate console to stabilize the surface temperature of the material at a set temperature. The temperature is calibrated by a temperature sensor close to the surface of the material. The evaporation rate of the material at different temperatures is calculated by calculating the loss mass of the water container and the wetted area of the material surface, thereby solving the problem of large numerical error of the evaporation rate caused by temperature offset of the heating plate under high temperature conditions.
[0040] 4. The embodiments of the present invention provide a testing device and method for a Ti-6Al-4V material with efficient heat dissipation performance. During the test, the water film on the surface of the material maintains a dynamic balance. The water film state in different wetting areas of the material is photographed by a high-speed camera and an infrared thermal imager. For the first time, the captured microscopic-scale surface water film image is combined with the thin film evaporation theory, which explains from a microscopic scale why the Ti-6Al-4V material maintains efficient evaporation under high temperature conditions. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] Figure 1 The present invention provides a preferred embodiment Figure 1 Surface 3D image, cross-sectional profile image and SEM (electron microscope) image of the Ti-6Al-4V material with high heat dissipation performance provided by the embodiment of the present invention;
[0042] Figure 2 The evaporation rate of the Ti-6Al-4V material with high heat dissipation performance measured at different temperatures provided by the embodiment of the present invention;
[0043] Figure 3 High-speed camera image and infrared thermal imager image of the Ti-6Al-4V material with high heat dissipation performance provided by the embodiment of the present invention at 230°C;
[0044] Figure 4 A schematic diagram of the structure of an evaporation rate testing device provided in an embodiment of the present invention;
[0045] Figure 5 Comparison of cooling effects of M-cycle heat and mass exchangers assembled from Ti-6Al-4V materials with high heat dissipation performance at different temperatures and wind speeds provided by the embodiments of the present invention;
[0046] Figure 6 Schematic diagram of the structure of the M-cycle heat and mass exchanger according to an embodiment of the present invention. DETAILED DESCRIPTION
[0047] The following will describe the technical solutions in the embodiments of the present invention in detail in conjunction with the accompanying drawings in the embodiments of the present invention. The described embodiments are only part of the embodiments of the present invention.
[0048] The technical solution of the present invention to solve the above technical problems is:
[0049] The present invention aims to solve the problem that high-temperature M-cycle cooling technology application materials are difficult to dissipate heat stably and efficiently under high temperature conditions. Based on this, a preparation method, application, and testing device and method of high-temperature heat dissipation material Ti-6Al-4V are provided. After the Ti-6Al-4V material is ablated by a femtosecond laser, specific micro- and nanostructures will be formed on the surface of the material, such as micron-scale V-shaped grooves. These grooves are also distributed with nanoscale structures. These microstructures can increase the surface area of the material, allowing more liquid to spread on the surface of the material, thereby improving the efficiency of evaporative heat dissipation. In addition, the V-shaped grooves on the surface of the Ti-6Al-4V material and the rich micro-nano structures on the grooves also provide extremely strong capillary forces, which can vertically pump water in a water container against gravity to the surface of the material. Even in a high temperature environment above 230°C, it can still exhibit super-wetting properties and maintain a high evaporation rate, thereby meeting the needs of stable heat dissipation in a high temperature environment.
[0050] Ti-6Al-4V is a titanium alloy material widely used in the field of heat dissipation. It has high strength and low density, good corrosion resistance, thermal conductivity, low thermal expansion coefficient and excellent fatigue resistance, which makes this material have advantages in the field of heat dissipation. More importantly, the excellent machinability of Ti-6Al-4V material allows the design of complex heat dissipation structures (such as heat sinks, heat exchangers, etc.). This flexibility makes Ti-6Al-4V material suitable for different heat dissipation designs, greatly expanding its application in the field of high-temperature heat dissipation.
[0051] Example 1
[0052] The embodiment of the present invention provides a Ti-6Al-4V material with high-efficiency heat dissipation performance at high temperature. The Ti-6Al-4V material is characterized by a series of parallel V-shaped grooves under a 3D confocal microscope, with a groove depth of 50 to 60 μm and a spacing of 90 to 100 μm between adjacent grooves. In addition, under the characterization of an electron microscope (SEM), the V-shaped grooves have abundant irregularly distributed nanopores, nanopillars, nanoclusters and other smaller-scale micro-nano structures.
[0053] Example 2
[0054] The embodiment of the present invention also provides a method for preparing a Ti-6Al-4V material with high-efficiency heat dissipation performance at high temperature, comprising the following steps:
[0055] (1) Ti-6Al-4V used for femtosecond laser ablation is composed of titanium: 90.7%-91.7%, aluminum: 5.5%-6.75%, and vanadium: 3.5%-4.5%, with a thermal expansion coefficient of 8.6×10 -6 / K, density is 4.43g / cm 3, high temperature melting point is above 1660℃, hardness is 300HB, specific heat capacity is 0.52J / g·K, size is 25×50mm, thickness is 1mm.
[0056] (2) A femtosecond laser processing experimental platform was built in a dust-free environment with a temperature of 23°C and a relative humidity of 50%. The femtosecond laser used was from Astrella Corporation in the United States. The laser amplification system generated 83fs pulses with an energy of approximately 7mJ per pulse and a central wavelength of 800nm.
[0057] (3) The polished Ti-6Al-4V was placed in an ultrasonic cleaner for cleaning for 3 minutes and then taken out and fixed on an XYZ three-dimensional displacement platform with precise control of movement. The three parameters of the displacement platform movement distance, speed, and step length were precisely controlled by programming with LabVIEW. The femtosecond laser was started to ablate the surface of the Ti-6Al-4V material. The processing parameters were as follows: laser energy density was 7 / cm 2 The step length between scanning lines is 100μm, the pulse repetition frequency is 1000Hz, the scanning speed is 0.5mm / s, and the area of the processing area is 20×45mm; after processing, a three-dimensional laser scanning microscope (VK-X1100) and an electron microscope (SEM) are used to study the structure of the material surface.
[0058] like Figure 1 The 3D image (c) and cross-sectional profile (e) of the Ti-6Al-4V material surface clearly show the V-shaped grooves after ablation on the material surface. The depth of these grooves is about 56 μm, and the spacing between adjacent grooves is about 90 μm. In addition, a large number of irregularly distributed micro-nano structures are observed on the groove surface in the electron microscope images (a, b, d) with a larger magnification. These micro-nano structures enable the Ti-6Al-4V material to have a strong capillary pumping force and an efficient evaporation rate at high temperatures.
[0059] Example 3
[0060] In order to test the evaporation rate of the Ti-6Al-4V material after femtosecond laser ablation at high temperature in Example 2 and analyze the cooling effect of the material, a Figure 5 Evaporation rate test apparatus shown:
[0061] High-precision balance: Zhuojing electronic analytical balance produced by Shanghai Zhuojing Company, model BS1204, maximum weighing is 120g, minimum weighing is 0.1mg, weighing pan size is Ф90 (inner diameter), accuracy level:
[0062] Ⅰ, Net weight (approx.): 4.0kg.
[0063] Temperature sensor: GM1312 thermocouple thermometer produced by Shenzhen Jumaoyuan Technology Co., Ltd. The temperature measurement range of the host is -200-1372°C; resolution 0.1t<1000°; 1.0t≥1000°; accuracy ±0.1%+0.6°C; size 72×29×145.5mm. The measurement range of K-type thermocouple is 0-250°C; tolerance is 2.5°C or 0.75%t, Class II; thermal response time <10 seconds.
[0064] Heating plate: PTC constant temperature heating plate produced by Weihua Electronic Technology Co., Ltd., the surface constant temperature can be set up to 270℃, the size is 30×6×100mm.
[0065] Heating plate control console: Autonics brand TCN4S-24R model intelligent temperature controller represented by Shenzhen Aozhengtong Automation Co., Ltd. Display mode: 4-digit 7-segment LED; Control output: relay + SSR drive output; Power supply voltage: 100-240VAC~50 / 60Hz.
[0066] High-speed camera: The Phantom VEO 710L high-speed camera, from the United States, is equipped with an advanced 280×800 CMOS sensor with a full-frame shooting rate of up to 7400 frames per second. This camera has excellent sensitivity (ISO) and supports 1280×800 resolution at 7400 frames per second at the 1 million pixel level, with a data transmission rate of 7Gpx / s. In addition, its maximum shooting rate is 680,000 frames per second, and the minimum exposure time is only 300ns. The camera is also equipped with a large memory capacity of 72GB to meet various high-speed shooting needs.
[0067] Infrared thermal imager: ImageIR scientific-grade infrared thermal imager uses a high-end 640x512 pixel MCT detector, achieving a full-frame imaging rate of up to 232Hz. The device not only has a fast imaging speed, but also has excellent thermal sensitivity, temperature measurement accuracy and high resolution.
[0068] The experimental environment was a clean room with a temperature of 23°C (±0.5°C) and a relative humidity of 50% (±2%).
[0069] exist Figure 5In the device shown, the material is placed vertically and parallel to the heating plate, and the lower part of the material is placed in a water container with an opening size of only 23×2mm; high-temperature resistant PTFE material is used to place the temperature sensor close to the ablation area of the material in the upper right corner of the material; 90% to 95% of the capacity of deionized water is injected into the rectangular water container to supply water for evaporation of the sample under high temperature conditions; a high-speed camera is placed directly opposite the material, an infrared thermal imager is placed at the lower end of the high-speed camera, and fill-light LED lights are placed on the left and right sides of the material to observe the water film state in different areas of the material.
[0070] like Figure 3 As shown in the figure, high-speed camera micrographs (a, b), images under ordinary optical lenses (c), and infrared thermal imagers (d) of different wetting areas of the material at 230°C are given. As shown in the ordinary optical lens image (c), more than 45% of the area is still in a wetting state, and from the high-speed camera micrographs (a, b), the wetting of the surface of the Ti-6Al-4V material under high magnification is clearly observed. The thin film wetting area and the ultra-thin film wetting area on the surface of the Ti-6Al-4V material account for more than 70% of the entire wetting area. In addition, the infrared thermal imager image (d) clearly observes the difference in temperature between the wetting area and the non-wetting area. Thanks to the super-wetting properties of the material, a large amount of heat in the wetting area of the material is evaporated away, making the material show good heat dissipation performance.
[0071] In order to obtain the specific evaporation value of the Ti-6Al-4V material, the present invention adopts the evaporation rate test method of the above device, comprising the following steps:
[0072] 1) Clamp the sample vertically against the heating plate, and place a partially open rectangular water container at the lower end;
[0073] 2) Place high temperature resistant PTFE material in a small area on the upper right side of the sample to make the temperature sensor close to the sample;
[0074] 3) Heat the heating plate close to the material to the set temperature through the heating plate control console;
[0075] 4) Inject 90% to 95% of the capacity of the rectangular water container with deionized water, record the initial mass m1 of the water container, make the water container contact the bottom of the material, and record the starting time t1;
[0076] 5) Record the wetted surface area S1 of the sample;
[0077] 6) Record the stopping time t2 and quickly measure its mass m2;
[0078] 7) Calculate the evaporation rate of Ti-6Al-4V material at different temperatures according to the formula:
[0079]
[0080] like Figure 2 As shown in the figure, at different temperatures set by the heating plate console, the specific evaporation rate values were obtained through testing. The evaporation rate of the liquid on the surface of the material is extremely high, which can effectively take away a lot of heat. As the temperature rises, the evaporation rate of the material surface also increases, which shows that the material still maintains excellent wetting properties and efficient evaporation capabilities under high temperature conditions, thereby showing strong heat dissipation performance under high temperature conditions, so it can be used as an application material for high-temperature M-cycle cooling technology.
[0081] Example 4
[0082] In order to verify the feasibility of Ti-6Al-4V material as a high-temperature M-cycle cooling technology material, the present invention also designs the following Figure 5 The M-cycle heat and mass exchanger shown:
[0083] The lower end of the material is supplied with water by a rectangular water reservoir, and 40 pieces of Ti-6Al-4V materials ablated by femtosecond laser are evenly placed in two water reservoirs. A digitally controlled hot air gun is used to control hot air with different wind speeds and temperatures to blow in from the air inlet. A wind speed probe is placed at the air inlet to detect the wind speed at the air inlet, and a temperature sensor is placed at the air inlet to detect the air inlet temperature. The hot air blown out by the hot air gun passes through the M-cycle cycle of the two middle air chambers. The upper end of the first air chamber discharges humid air, and the cooled cold air is discharged at the leftmost air outlet. A second temperature sensor is placed at the air outlet to obtain the real-time temperature of the cooling air at the air outlet.
[0084] Use Omega's Logging Software to get the temperature of the air inlet and outlet and the overall wind speed in real time. Figure 4 As shown in the figure, as the inlet temperature continues to rise, even if the outlet temperature is also rising, the rise is extremely slow. At a wind speed of 1.25m / s, the inlet air temperature is as high as 330℃, while the outlet cooling air temperature is below 26℃. It is also worth noting that Figure 4 It can be seen that as the inlet wind speed decreases, the cooling efficiency of the outlet air temperature is greatly improved. It can be believed that reducing the wind speed within a certain range can further improve the cooling efficiency.
[0085] In view of the cooling efficiency data tested by the above M-cycle heat and mass exchanger, the 330℃ hot air was cooled to below 26℃, showing a strong high-temperature cooling effect, proving that the Ti-6Al-4V material ablated by femtosecond laser can well complete the heat dissipation task as the cooling material of M-cycle technology under high temperature conditions, reflecting the excellent wetting performance and efficient heat dissipation effect of Ti-6Al-4V material under high temperature conditions. It opens a new door for the application of M-cycle technology in high temperature fields.
[0086] The systems, devices, modules or units described in the above embodiments may be implemented by computer chips or entities, or by products with certain functions. A typical implementation device is a computer. Specifically, the computer may be, for example, a personal computer, a laptop computer, a cellular phone, a camera phone, a smart phone, a personal digital assistant, a media player, a navigation device, an email device, a game console, a tablet computer, a wearable device, or a combination of any of these devices.
[0087] It should also be noted that the terms "include", "comprises" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method, commodity or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, commodity or device. In the absence of more restrictions, the elements defined by the sentence "comprises a ..." do not exclude the existence of other identical elements in the process, method, commodity or device including the elements.
[0088] The above embodiments should be understood to be only used to illustrate the present invention and not to limit the protection scope of the present invention. After reading the contents of the present invention, technicians can make various changes or modifications to the present invention, and these equivalent changes and modifications also fall within the scope defined by the claims of the present invention.
Claims
1. A high temperature heat dissipation material Ti-6Al-4V, characterized in that: The titanium-aluminum-vanadium alloy Ti-6Al-4V material is composed of titanium: 90.7%-91.7%, aluminum: 5.5%-6.75%, and vanadium: 3.5%-4.5%, and has a thermal expansion coefficient of 8.6×10 -6 / K, its density is 4.43g / cm 3 , high temperature melting point is above 1660℃, hardness is 300HB, specific heat capacity is 0.52J / g·K.
2. The high temperature heat dissipation material Ti-6Al-4V according to claim 1, characterized in that: The surface of the Ti-6Al-4V material has a plurality of parallel and continuously distributed V-shaped grooves, the groove depth of the Ti-6Al-4V material is 50-60 μm, the spacing between adjacent grooves is 90-100 μm, and the groove surface of the material has a rich micro-nano structure of 10 nm to 200 μm.
3. The high temperature heat dissipation material Ti-6Al-4V according to claim 1, characterized in that: The material Ti-6Al-4V is processed by femtosecond laser ablation; the femtosecond laser ablation is carried out in a dust-free room with a constant temperature of 23° C. and a constant humidity of 50%.
4. The high temperature heat dissipation material Ti-6Al-4V according to claim 3, characterized in that: The femtosecond laser ablation parameters are: laser energy density 7J / cm 2 , the step length between scan lines is 100 μm, the pulse repetition frequency is 1000 Hz, and the scanning speed is 0.5 mm / s.
5. A method for preparing the material Ti-6Al-4V according to any one of claims 1 to 4, characterized in that: The steps include: (1) The polished Ti-6Al-4V material was placed in an ultrasonic cleaner and cleaned with deionized water for 3 minutes; (2) Place the cleaned and polished Ti-6Al-4V material on a femtosecond laser displacement platform; (3) In a clean room with a constant temperature of 23°C (±0.5°C) and a constant relative humidity of 50% (±2%), a femtosecond laser was used to ablate the surface of the Ti-6Al-4V material; the laser ablation parameters were: laser energy density 7 J / cm 2 , the step length between scanning lines is 100 μm, the pulse repetition frequency is 1000 Hz, the central wavelength is 800 nm, and the scanning speed is 0.5 mm / s; (4) A Ti-6Al-4V material having a plurality of parallel and continuously distributed groove structures is obtained, wherein the groove depth is 50 to 60 μm and the spacing between adjacent grooves is 90 to 100 μm.
6. An application of the material Ti-6Al-4V according to any one of claims 1 to 4, characterized in that: The material Ti-6Al-4V is used for heat dissipation in a high-temperature M-cycle heat and mass exchanger.
7. An evaporation rate testing device based on the material Ti-6Al-4V according to any one of claims 1 to 5, characterized in that: include: High-precision balance, temperature sensor, heating plate, heating plate console, high-speed camera and infrared thermal imager: wherein the high-precision balance is used to accurately measure the mass m1 of deionized water before evaporation and the mass m2 of deionized water after evaporation in the water container; the temperature sensor is used to detect the real-time surface temperature of the Ti-6Al-4V material during the evaporation process, and calibrate the digital temperature displayed on the heating plate console to ensure the accuracy of the material surface temperature; the heating plate is used to provide heat to the Ti-6Al-4V material close to the heating plate; the heating plate console is used to digitally control the heating of the Ti-6Al-4V material by the heating plate, so that the surface temperature of the material is stably maintained at the set temperature, the high-speed camera is used to observe the water film state of different wetting areas on the surface of the Ti-6Al-4V material under high temperature conditions, and the infrared thermal imager is used to observe the temperature gradient distribution on the surface of the Ti-6Al-4V material under high temperature conditions.
8. A testing method based on the evaporation rate testing device according to claim 7, characterized in that: The steps include: 1) Clamp the sample vertically against the heating plate, and place a partially open rectangular water container at the lower end; 2) Place high temperature resistant PTFE material in a small area on the upper right side of the sample to make the temperature sensor close to the sample; 3) Heat the heating plate close to the material to the set temperature through the digital visual heating table controller; 4) Inject 90% to 95% of the capacity of the rectangular water container with deionized water, record the initial mass m1 of the water container, make the water container contact the bottom of the material, and record the starting time t1; 5) Record the wetted surface area S of the sample 1; 6) Record the stopping time t2 and quickly measure its mass m2; 7) Calculate the evaporation rate of Ti-6Al-4V material at different temperatures and wind speeds according to the formula: 8) Use a high-speed camera and an infrared thermal imager to observe and record the water film state in different areas of the sample.
Citation Information
Patent Citations
A high thermal stability equiaxed nanocrystalline Ti6Al4V-Fe alloy and its preparation method
CN112063893B
A high thermal stability equiaxed nanocrystalline Ti6Al4V-Ni alloy and its preparation method
CN112251635B
Processing method for improving low-temperature superplasticity of Ti-6Al-4V alloy
CN108677116A
Super-wetting material as well as preparation method and application thereof
CN114459881A
Method and system for measuring evaporation rate of silicon material
CN115575277A
Cited By
Silicon carbide ceramic material with super wettability at high temperature, preparation method, application and testing device and method
CN116174926A